Study of the structural, optical, and morphological properties of ZnO nanoparticle biosynthesis using betel leaf extract as a bioreductant - Hamzah, Yanuar; Kartika, Nursiti Sari; Umar, Lazurdi (Universitas Riau, 2024)
The biosynthesis of zinc oxide nanoparticles (ZnO) is extensively studied because of its eco-friendly and simple method. Piper ornatum is abundant in Indonesia, and the phytochemical content of Piper ornatum leaves has the potential to be a reductor. The study aims to study the role of Piper ornatum in biosynthesis and the characteristics of the zinc oxide nanoparticles. The sample variations in this study were the volume of Piper ornatum and the precursor solution of zinc nitrate hexahydrate Zn(NO3)2·6H2O in proportions of 1:1, 1:5, and 1:10. Characterizations performed include UV-Vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy, energy dispersive X-ray spectroscope and blue methylene degradation test. UV-Vis spectroscopy of all samples showed peak absorption at the interval of 250 – 330 nm, which indicates that ZnO nanoparticles have already formed. The results of characterization using XRD indicated the degree of crystallinity of the ZnO nanoparticles is not perfect because the crystal field (100) or the highest diffraction peak has a very large full width at half maximum value of 0.8187°. Characterization results using SEM indicate an inhomogeneous morphology and the presence of zinc oxide nanoparticle agglomeration where particle size distribution is at an interval of 170 – 758 nm.